Age-specific incidence of injury-related hospital contact after release from prison: a prospective data-linkage study. Issue 3 (30th March 2019) - Young, Jesse T; Borschmann, Rohan; Preen, David B; Spittal, Matthew J; Brophy, Lisa; Wang, Emily A; Heffernan, Ed; Kinner, Stuart A
Abstract : Background: In population studies, the risk of injury declines after early adulthood. It is unclear if a similar age difference in the risk of injury exists among people released from prison. Methods: Prerelease survey data collected between 1 August 2008 and 31 July 2010, from a representative cohort of sentenced adults (≥18 years) in Queensland, Australia, were linked prospectively and retrospectively to person-level emergency department, inpatient hospital and correctional records. To ascertain predictors of injury-related hospital contact, we fit a multivariate Andersen-Gill model and tested the interactions between age group (<25 years, ≥25 years) and each variable. Results: In 1307 adults released from prison, there were 3804 person-years of follow-up. The crude injury rate was 385 (95% CI 364 to 407) per 1000 person-years and did not differ according to age group. Factors associated with increased injury-related hospital contact included a history of mental illness, preincarceration injury, a history of incarceration, release from a short prison sentence (<90 days), being reincarcerated during follow-up and identifying as Indigenous. The effect of mental illness, risky alcohol use, prior incarceration and intellectual disability differed across age group and predicted increased risk of injury among people aged ≥25 years compared with their counterparts without these characteristics. Conclusions: Unlike in the general population where the risk of injury declines with age, older adults released from prison are at similar risk compared with their younger peers. Adults released from prison with mental illness, a history of injury-related hospital contact and who identify as Indigenous are particularly indicated groups for injury prevention.